Limit Criteria of Post-Tensioned Thin Web Beams - Lee, Teang Shui (1989)
A total of 45 partially prestressed post-tensioned thin web T-be answered tested to investigate their ultimates hear and flexural strengths and the service ability limit so reflection and crack width. The varying para meters included in the study are the amount of prestress, amount of supplementary nonprestressed reinforcements, prestressing tendons being bonded or unbonded, absence or presence of shear reinforcements and width of the web. Astrain compatibility method with the associated bond factors is presented for the ultimate flexural strength analysis of the beams. For prediction of the oreticalloads, material characteristics are taken at their ultimate with no materials safety factor associated.